2014
DOI: 10.1155/2014/796565
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Adiponectin on Periodontal Ligament Cells under Normal and Regenerative Conditions

Abstract: Type 2 diabetes and obesity are increasing worldwide and linked to periodontitis, a chronic disease which is characterized by the irreversible destruction of the tooth-supporting tissues, that is, periodontium. The mechanisms underlying the association of diabetes mellitus and obesity with periodontal destruction and compromised periodontal healing are not well understood, but decreased plasma levels of adiponectin, as found in diabetic and obese individuals, might be a critical mechanistic link. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 83 publications
(93 reference statements)
0
32
0
2
Order By: Relevance
“…On the other hand, adipokines like adiponectin, leptin or visfatin have been also shown to be produced in periodontal cells, to be regulated by periodontopathogenic bacteria and to influence the regenerative mechanisms of periodontal cells (Nokhbehsaim et al. , ,b, Deschner et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, adipokines like adiponectin, leptin or visfatin have been also shown to be produced in periodontal cells, to be regulated by periodontopathogenic bacteria and to influence the regenerative mechanisms of periodontal cells (Nokhbehsaim et al. , ,b, Deschner et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a positive effect of total adiponectin on skin keratinocyte proliferation has been reported in mice where adiponectin was directly associated with cutaneous wound healing (Shibata et al, 2012), and this effect was confirmed in human periodontal ligament (PDL) cells (Nokhbehsaim et al, 2014). However, a study in human gingival keratinocytes (GK) found no effect of total adiponectin alone on cell proliferation and an inhibitive effect in combination with P. gingivalis LPS (Kraus et al, 2012).…”
Section: Strengths and Limitationsmentioning
confidence: 98%
“…Furthermore, the gingival tissues showed significantly reduced expression of adiponectin in periodontitis, although no change was observed for its receptors compared to the control group. Interestingly, a study from our group showed that P. gingivalis suppresses adiponectin expression in PDL cells while stimulating the expression of its receptors [37]. Also, downregulation of adiponectin and increased expression of its receptors have been observed in gingival tissues of periodontal patients as compared to periodontal healthy ones [31].…”
mentioning
confidence: 93%